Radiographic Correction Following Reconstruction of Adult Acquired Flat Foot Deformity Using the Cotton Medial Cuneiform Osteotomy. (May 2016) - Aiyer, Amiethab; Dall, Graham F.; Shub, Jeffrey; Myerson, Mark S.
Background: The Cotton osteotomy has been used to correct residual forefoot supination in flexible flatfoot deformity reconstruction. The purpose of this study was to delineate the radiographic effects of the Cotton osteotomy by controlling for concomitant procedures used for deformity correction. Methods: We retrospectively analyzed 67 patients who underwent a Cotton osteotomy as part of a flatfoot reconstructive procedure. We evaluated 12 radiographic parameters including the articular surface angles of the foot, Meary angle, and a newly defined medial arch sag angle (MASA). Twenty-eight of these patients were matched to a cohort that did not undergo a Cotton osteotomy. Results: In all patients who underwent a Cotton osteotomy, there were statistically significant changes in the articular surface angles and medial arch height ( P < .05). No radiographic secondary sag of the medial column was seen at final follow-up. Compared to 28 matched controls, the Cotton osteotomy did not improve Meary angle but provided an additional 6.5 degrees correction of the MASA ( P = .002). After reliability testing, the intraclass correlation coefficient was found to be substantial for the MASA compared to Meary angle. Discussion: The data suggest that the MASA was a useful radiographic tool for assessing midfoot collapse in the setting of pes planovalgus. The current study demonstrated the corrective capacity of the Cotton osteotomy on the MASA; at final follow-up, there was no evidence of radiographic instability. This is suggestive that a naviculocuneiform arthrodesis may not be warranted for medial column stabilization in the setting of flatfoot reconstruction. Level of Evidence: Level III, case control study.